Perceived partial social integration, levels of distress and resilience, and COVID-19 vaccine rejection of Jewish and Arab citizens of Israel - Yohanan Eshel; Shaul Kimhi; Hadas Marciano; Bruria Adini (Frontiers in Public Health, 2022)
IntroductionThe present study examines the role of perceived partial social integration (PPSI) in determining the rejection of the COVID-19 vaccine of Jewish and Arab citizens of Israel.MethodsThe research hypotheses are examined using a relatively large sample of the Israeli public, including 208 Arab and 600 Jewish adults, who have responded to an anonymous questionnaire pertaining, among other issues, to partial social integration and the individual level of vaccine uptake.ResultsHigher levels of PPSI were found to be associated with higher levels of vaccine rejection, in both Jewish and Arab samples. The Arab minority group regards themselves as less socially integrated into the Israeli society and therefore rejects the COVID-19 vaccine to a greater extent than the majority group. The Arab respondents expressed a higher level of psychological distress and a lower level of resilience compared with the Jewish participants. The perceived partial social integration score significantly predicted the levels of distress and resilience of the Jewish but not the Arab sample.DiscussionThe study indicates that increasing the vaccination rates depends more substantially on trust in the authorities than on leveraging greater pressure on individuals that reject the vaccine. Increased trust in the authorities and regarding oneself as an integral component of society are two vital conditions for vaccine acquiescence. Insufficient social integration is a major reason for vaccine rejection.